Deposit Dollarization and the Financial Sector in Emerging Economies - Honohan, Patrick; Shi, Anqing (World Bank, Washington, DC, 2014)
Analyzing new data, the authors find that the general trend toward increased use of foreign-currency-denominated bank deposits in emerging markets has continued, despite declines in a few countries. Their analysis of the new data suggests that a sizable fraction (about half, on average) of funds switched to dollar deposit accounts are effectively exported through the banking system, thereby reducing the supply of credit. Moreover, increases in deposit dollarization are associated with increases in offshore deposits, which probably helps to explain the authors' finding that dollarization is associated with an increase in banking spreads. The authors' evidence supports, though only weakly, the conjecture that dollarization would tend to raise wholesale interest rates systematically through a peso premium. In contrast, greater dollarization is clearly associated with a higher pass-through coefficient from exchange rate change to consumer prices, potentially increasing nominal risk in the economy.